Enhancing resiliency and optimizing readiness in military personnel through psychological flexibility training: design and methodology of a randomized controlled trial - Peterson, Alan L.; Moore, Brian A.; Evans, Wyatt R.; Young-McCaughan, Stacey; Blankenship, Abby E.; Straud, Casey L.; McLean, Christopher S.; Miller, Tashina L.; Meyer, Eric C.; , for the STRONG STAR Consortium (Frontiers in Psychiatry, 2024)
Background: Enhancing resiliency and optimizing readiness in military personnel is a high priority for the U.S. Department of Defense. Most military resiliency-enhancement programs are evidence-informed interventions. However, few randomized studies have demonstrated efficacy of any intervention or training program to enhance resiliency and prevent the development of psychological health symptoms in military personnel when exposed to operational stressors. This manuscript provides an overview of the theoretical foundation, research design, and research methods of a preventive intervention trial designed to evaluate the efficacy of a training program to enhance resiliency and prevent psychological health symptoms in military personnel. The resiliency training intervention is based on Acceptance and Commitment Therapy (ACT), an evidence-based intervention with broad empirical support for improving functioning in those living with psychological and medical conditions. Method/Design: This study will evaluate the efficacy of a two-day training program based on ACT for fostering psychological flexibility, the central target in ACT, for enhancing resiliency, and for preventing the development of psychological health symptoms. The research participants will be a non-clinical population of active duty military personnel (N = 600). The ACT-based training program (n = 300) will be compared to a military resiliency training as usual, known as Master Resilience Training (n = 300). Assessment measures will be administered at the baseline assessment, after training, prior to a military deployment, and after returning from a deployment. Qualitative interviews will be conducted to provide feedback on the training program.